An Explanation of the Psycho-Social Factors Driving Child Sexual Perpetrators Towards Sexual Abuse in Khyber Pakhtunkhwa (Journal of Asian Development Studies, 2024)
Child Sexual Abuse (CSA) is a severe global child rights issue. This native research finding is the first of its kind and will explore the persuading factors and pave the way for future research exploration. The study explores the psychosocial factors driving perpetrators to commit child sexual abuse. The integrated theory of sexual offending by Ward and Beech 2002 guided the research. This study used a phenomenological qualitative methodology and purposive sampling to select participants. Twenty-five child sexual perpetrators were interviewed in a private room at central jail, Peshawar, after receiving formal approval from jail authorities and verbal consent from the participants. They were allowed to withdraw from the interview at any time. Data collection involved 60 to 80-minute in-depth interviews guided by a structured protocol. Ethical standards, including verbal informed consent and ensuring anonymity and confidentiality, were strictly adhered to throughout the research process. NVIVO software was used for thematic analysis. The analysis revealed a myriad of psychosocial factors influencing perpetrators, such as childhood victimization, substance abuse, cognitive distortions, notions of masculinity, delayed marriage, sexual gratification, social isolation, and exposure to pornography. Perpetrators are often familiar faces within the child's and family's proximity, typically with no prior convictions and mostly first-time offenders. The study highlights the complex interplay of psychosocial factors that drive perpetrators to child sexual abuse.